Experimental and numerical evaluation of compression confinement techniques for HSC beams reinforced with different ratios of high strength steel reinforcement (Fracture and Structural Integrity, 2022)
This work presents experimental and numerical research to evaluate the compression confinement techniques of HSC beams reinforced with different ratios of high-strength steel reinforcement. Twelve specimens of high-strength reinforced concrete beams with two different compression confinement techniques were tested experimentally. The first method is used carbon fiber reinforced polymers sheets (CFRPs) around the compression zone, CF, and the steel fibers reinforced concrete is used in the compression zone by 1% of volume fraction, SF, in the second case. A 3-D finite element analysis was done; using the ANSYS program to simulate and idealize all experimental specimens. The numerical and experimental results of the RC beams were validated and compared in this work. The results showed that there is a good idealization using 3-D finite element models with the experimental specimens. Also, it was found that using the suggested techniques can increase the strength ratio and increase the ductility index depending on the tensile reinforcement ratios. Moreover, the energy absorption and the mode of failure were enhanced.
Keywords: HSC beams; confinement techniques; ANSYS; Carbon fiber reinforced polymers; Steel fiber; Ductility; Mode of failure